Effect of Rapid Thermal Annealing on the Electrical Properties of GaAs Schottky Diodes Embedded with Self-Assembled InAs Quantum Dots - Colleaux, Florian; Lee, Jungil; Yu, Byung Yong; Han, Ilki; Choi, Won Jun; Song, Jin Dong; Ghibaudo, Gerard (AMER SCIENTIFIC PUBLISHERS, 2008)
After rapid thermal annealing (RTA), deep levels were found to be generated in Au/GaAs Schottky diodes embedded with InAs quantum dots grown by migration enhanced molecular beam epitaxy (MEMBE). From the corner frequency of the 1/f(2) part of the low-frequency noise specrtral density, the locations of the deep levels were estimated to be 0.58, 0.61, and 0.66 eV below the conduction band edge for the samples without quantum dot layer, with quantum dot layer and capping layer thickness of 0.8 mu m, and with quantum dot layer and the capping layer thickness of 0.4 mu m, respectively. RTA also lowered the Schottky barrier height.